2017
DOI: 10.1080/14767058.2017.1297401
|View full text |Cite
|
Sign up to set email alerts
|

Uterine rupture after previous low segment transverse cesarean is rarely catastrophic

Abstract: Cautious selection and close monitoring of candidates are the cornerstones of successful management of TOLAC. Readily available facilities for emergency cesarean delivery and concerted obstetrical team can save the mother and child from catastrophic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 4 publications
0
15
0
4
Order By: Relevance
“…Our results are partially consistent with the previous study that uterine rupture after previous low segment transverse caesarean is rarely catastrophic, and pregnant women with previous transverse CS having trial of vaginal birth have low risk of uterine rupture. [ 7 ] In our series, although 9.34% pregnant women with previous CS occurred LUS rupture in this study, there were no severe maternal and neonatal events. Three pregnant women with previous CS had spontaneous vaginal birth unexpectedly, and no uterine rupture occurred.…”
Section: Discussionmentioning
confidence: 46%
“…Our results are partially consistent with the previous study that uterine rupture after previous low segment transverse caesarean is rarely catastrophic, and pregnant women with previous transverse CS having trial of vaginal birth have low risk of uterine rupture. [ 7 ] In our series, although 9.34% pregnant women with previous CS occurred LUS rupture in this study, there were no severe maternal and neonatal events. Three pregnant women with previous CS had spontaneous vaginal birth unexpectedly, and no uterine rupture occurred.…”
Section: Discussionmentioning
confidence: 46%
“…Unfortunately, we have no such tool, and the SMFM calculator cannot be repurposed to this end. This is because few unsuccessful TOLACs result in uterine rupture, and few uterine ruptures result in permanent damage . Unfortunately, these rare outcomes are simply unpredictable for individual women and must be balanced against the immediate and long‐term risks of repeat cesareans.…”
Section: Predicting Disastermentioning
confidence: 99%
“…More recently, Scifres et al, using similar data, attempted to develop an algorithm that distinguishes women at risk for a composite outcome of uterine rupture, bladder injury, and bowel injury associated with TOLAC. Like Macones and Grobman, Scifres et al identified individual variables statistically associated with their composite. Despite having a large sample of women (13,706 women undergoing TOLAC and 300 composite morbidities), they could not reliably predict the composite outcome for individual women (the AUC was 0.65).…”
Section: Predicting Disastermentioning
confidence: 99%
“…This finding suggests that the reduction in women undergoing TOLAC does not reflect improved selection of patients for VBAC [3,13]. Success rates for TOLAC range from 28 to 85% [3,[14][15][16] and are higher for women with a previous CS for nonrecurring indications, such as breech presentation, and for women with a previous vaginal birth [17][18][19][20]. Furthermore, TOLAC is supported by obstetrical best practice guidelines in numerous countries [7,9,11,21].…”
Section: Introductionmentioning
confidence: 99%